Knowledge and use of biocultural diversity by Nahua in the Huasteca region of Hidalgo, Mexico - Gutiérrez-Santillán, Tania Vianney; Moreno-Fuentes, Ángel; Sánchez-González, Arturo; Sanchez-Rojas, Gerardo (Ethnobiology and Conservation, 2019)
The Huasteca region of Mexico is one of the most biologically and culturally diverse in the country. In this study, we set out to identify and analyze biodiversity knowledge and use by two indigenous nahua communities located in two types of vegetation (tropical semi-evergreen forest [TSEF] and montane cloud forest [MCF]). The fieldwork was carried out from January 2011 to December 2012, and ethnobiological information was collected by combining the ethnographic percentage sampling method (10%) and the snowball method, applying multiple freelists to 125 informants. The ethnobiological data was analyzed using indices adapted from measures of ecological diversity, and multivariate methods. In the two communities, 409 ethnospecies were identified, corresponding to a total of 383 species. The TSEF contained greater ethnospecies richness than the MCF. Eleven use categories were identified, the most important being consumption (edible) uses. In general, the local people have considerable knowledge of the biological diversity in their territory. We found that vegetation types influence local knowledge; however, there are similarities between communities in the same cultural group and located in the same geographical region.